COVID-19-Related Restrictions and Quarantine COVID-19: Effects on Cardiovascular and Yo-Yo Test Performance in Professional Soccer Players - Albuquerque Freire, Lucas de; Tannure, Márcio; Sampaio, Márcio; Slimani, Maamer; Znazen, Hela; Bragazzi, Nicola Luigi; Aedo-Muñoz, Esteban; Sobarzo Soto, Dany Alexis; Brito, Ciro José; Miarka, Bianca (Frontiers in Psychology, 2020)
The present study aimed to verify the effects of the quarantine during a serious viral outbreak on the cardiovascular and performance associated with yo-yo test in a sample of professional soccer players. Twenty high-level soccer players (age: 26 ± 4 years-old, height: 179 ± 6 cm) were participate in this study. The Yo-Yo intermittent test was performed pre- and post- COVID-19 quarantine. The Yo-Yo intermittent test was performed in a random order. During each test, running performances of the soccer players were monitored using a portable 5-Hz GPS with 100Hz accelerometer and a paired t-test was conducted, p ≤ .05. The main pre- COVID-19 quarantine versus post- COVID-19 quarantine demonstrate that in relative distance (161.7 ± 5.9 > 141.1 ± 33.8 m/min), max speed (18.7 ± 0.9 > 18.2 ± 0.6 km/h), acceleration (60 ± 20 frequency > 52 ± 16 frequency), deceleration (34 ± 13 frequency > 27 ± 6 frequency), respectively. A multi-component soccer training program could be considered the most adequate for professional athletes, including aerobic, resistance, balance, coordination and specific power motor abilities with short running actions, accelerations and decelerations.